Thrombophilia, Inflammation, and Recurrent Pregnancy Loss: A Case-Based Review - Grandone, Elvira; Piazza, Gregory (Seminars in Reproductive Medicine, 2021)
Recurrent pregnancy loss (RPL) is defined as the loss of two or more pregnancies and is often multifactorial with the majority of miscarriages being due to aneuploidy and anatomic or physiological abnormalities. However, inherited or acquired thrombophilias have also been associated with RPL, albeit inconsistently. While inherited thrombophilias, such as factor V Leiden and prothrombin gene mutation, are relatively prevalent in women with RPL compared with the general population, a causal link has yet to be definitively established. Recently, systemic inflammation, as measured by high-sensitivity C-reactive protein, has also been hypothesized to play a role in infertility. Based on limited prospective trial data, antithrombotic therapy and antiplatelet agents have been proposed as possible tools for the prevention of RPL. Because of the multifactorial nature of RPL and infertility, various clinicians, as obstetricians and gynecologists, endocrinologists, hematologists, or vascular medicine specialists, may be requested to counsel these women. This, together with evidence gaps, frequently leads to distinctly different diagnostic and therapeutic recommendations, especially regarding thrombophilia testing and treatment. Using four case vignettes in this review, we critically appraise the literature and highlight how two clinicians from different subspecialties approach the relationship between RPL, inflammation, and thrombophilia.
Keywords: antithrombotic therapy; anticoagulation; recurrent pregnancy loss; thrombophilia; thrombosis